Comparison of Three CD3-Specific Separation Methods Leading to Labeled and Label-Free T Cells - Ronald Weiss (MDPI AG, 2021)
T cells are an essential part of the immune system. They determine the specificity of the immune response to foreign substances and, thus, help to protect the body from infections and cancer. Recently, T cells have gained much attention as promising tools in adoptive T cell transfer for cancer treatment. However, it is crucial not only for medical purposes but also for research to obtain T cells in large quantities, of high purity and functionality. To fulfill these criteria, efficient and robust isolation methods are needed. We used three different isolation methods to separate CD3-specific T cells from leukocyte concentrates (buffy coats) and Ficoll purified PBMCs. To catch the target cells, the Traceless Affinity Cell Selection (TACS®) method, based on immune affinity chromatography, uses CD-specific low affinity Fab-fragments; while the classical Magnetic Activated Cell Sorting (MACS®) method relies on magnetic beads coated with specific high affinity monoclonal antibodies. The REAlease® system also works with magnetic beads but, in contrast to MACS®, low-affinity antibody fragments are used. The target cells separated by TACS® and REAlease® are “label-free”, while cells isolated by MACS® still carry the cell specific label. The time required to isolate T cells from buffy coat by TACS® and MACS® amounted to 90 min and 50 min, respectively, while it took 150 min to isolate T cells from PBMCs by TACS® and 110 min by REAlease®. All methods used are well suited to obtain T cells in large quantities of high viability (>92%) and purity (>98%). Only the median CD4:CD8 ratio of approximately 6.8 after REAlease® separation differed greatly from the physiological conditions. MACS® separation was found to induce proliferation and cytokine secretion. However, independent of the isolation methods used, stimulation of T cells by anti CD3/CD28 resulted in similar rates of proliferation and cytokine production, verifying the functional activity of the isolated cells.